My Hijab Covers my Mane, Not My Mind: Challenges Facing South African Muslim Women Academics - Quraisha Dawood (African Journal of Inter-Multidisciplinary Studies)
Muslim women in South Africa constitute 1.6% of the population, yet they have and continue to contribute significantly to the economy, pursue political freedom and rise to the upper echelons of academia. Research reveals that the identity of South African Muslim women centres on Islamic principles, such as modesty and dietary requirements, and cultural roles, such as being a mother and a homemaker. Despite Muslim women being more visible through media in recent years, literature shows that many remain marginalised, misunderstood, and often discriminated against for not subscribing to the dominant culture of the Western workplace. The study explores the challenges Muslim women academics face in South African higher education institutions when fulfilling their professional roles while maintaining Islamic and cultural obligations. Viewed through the lens of social identity theory, the chapter provides insight into the lived experiences of seven Muslim women academics and how they navigate the often-exclusionary spaces of academia. It will also provide practical solutions which may mitigate marginalisation and promote inclusivity within the South African academic landscape.